Penerapan Manajemen Kredit Pada Program Kemitraan Dan Bina Lingkungan (Pkbl) Pt Pelindo II Cabang Palembang Melalui Karakter, Kondisi Usaha, Jaminan dan Penyebab Lainnya - Meilin Veronica (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2019)
Corporate Social Responsibility Program of PT PELINDO II Branch Palembang is a program to improve the ability of small businesses to become strong and independent through the use of funds from the profits of PT PELINDO II BranchPalembang. The purpose of this research was to determine the application of credit management in the corporate social responsibility program(PKBL) PT. PELINDO II (Persero) Branch Palembang through character, business conditions, guarantees and other causes. The research methodology used in this research was to distribute questionnaires to 34 fostered partners, 1 PKBL employee and 1 supervisor. The results of the study show that the character of the fostered partners is of the opinion that PT. PELINDO II branch Palembang will not suffer losses even if the credit received is not returned. Seen from the questionnaire sample where 30 fostered partners (88.2%) strongly agree that if the PKBL credit loan is not returned, PT. PELINDO II branch Palembang has nothing to lose, so it has a big role in causing a large amount of arrears. Suggestions for further research are eliminating miscommunication with fostered partners, coordinating with other state-owned enterprises, conducting surveys of fostered partners, making effective visits to fostered partner locations and selection of prospective foster partners must be done correctly and transparently.